2018
DOI: 10.15259/pcacd.23.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional-Technological Properties of Meat-and-Vegetable Emulsions With the Addition of Chitosan Derivatives

Abstract: This article provides data on the analysis of the properties of chitosan derivatives as a functional ingredient used in food technologies as a structure-forming agent, immunomodulator, enterosorbent of xantobiotics, anti-sclerotic and anti-arthritic factor, and as a regulator of the acidity of gastric juice. The expediency of the use of N-methylallyl-chitosan (chitosan derivative) as a substance that improves the functional-technological (moisture and fat-retaining power) and rheological properties of meat-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Shestopalova et al . (2018) also reported that an increase in the amount of chitosan derivatives added during the preparation of meat and vegetable emulsions enhanced the water/fat‐retaining ability, which, in turn, increased the viscosity due to the formation of ionic and hydrogen bonds. Therefore, it could be surmised that the observed improvements in water and fat binding ability through the addition of CMs could positively contribute to the improvement of emulsion stability in meat emulsion.…”
Section: Resultsmentioning
confidence: 96%
“…Shestopalova et al . (2018) also reported that an increase in the amount of chitosan derivatives added during the preparation of meat and vegetable emulsions enhanced the water/fat‐retaining ability, which, in turn, increased the viscosity due to the formation of ionic and hydrogen bonds. Therefore, it could be surmised that the observed improvements in water and fat binding ability through the addition of CMs could positively contribute to the improvement of emulsion stability in meat emulsion.…”
Section: Resultsmentioning
confidence: 96%
“…The main areas that educational institutions need to focus on are introduction of subject-oriented educational technologies, organization of training using massive open online courses, transition to active and project-based forms of learning, individualization of education and development and implementation of network educational programmes (Korableva et al, 2018;Kurbanova et al, 2018). Other important areas highlighted by some researchers are simulated teaching, integration of teachers' education in their activities and dual training programmes (Sapozhkov et al, 2016;Shestopalova et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Las principales áreas en las que los centros educativos deben centrar sus esfuerzos son: introducción de tecnologías educativas centradas en contenidos, organización de formación utilizando cursos abiertos masivos en línea, transición a formas de aprendizaje activas y basadas en proyectos, personalización de la educación y desarrollo e implementación de programas educativos en red (Korableva et al, 2018;Kurbanova et al, 2018). Otras áreas importantes destacadas por algunos investigadores son la educación simulada (simulaciones educativas), la integración de la formación del profesorado en sus actividades y los programas de educación dual (Sapozhkov et al, 2016;Shestopalova et al, 2018).…”
Section: Revisión De La Literaturaunclassified